Harmonizing Shari'ah Rulings in Islamic Finance: Strategies and Challenges - Shaharuddin, A. (Universiti Sains Islam Malaysia, 2024)
The main objective of this paper is to discuss the ways and challenges in harmonizing shari'ah rulings in Islamic finance industry. The issue of harmonization is pertinent to be resolved because of disagreements over certain shari'ah issues to certain extent has hindered industry's robust growth in the global market. This paper critically reviews previous efforts and proposes a new harmonization framework at national and international levels. Apart from that, it also identifies the main challenges in harmonizing shari'ah rulings. The challenges identified are the absence of inclusive participation in issuing shari'ah standards, lack of regulatory support, discrepancy level of industry development between countries, differences of shari'ah governance framework and difficulty to win over all shari'ah scholars collectively. This paper will be valuable addition to the existing literature in the effort towards enhancing the governance of shari'ah matters in Islamic finance industry.